2013
DOI: 10.1002/qj.2029
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the forecast skill of the Global Modeling and Assimilation Office Observing System Simulation Experiment

Abstract: The performance of the GMAO OSSE in terms of forecast skill and observation impacts is evaluated against real observational data for the same period. Metrics of anomaly correlation of 500 hPa geopotential and root-mean-square error of temperature and wind fields for 120 h forecasts are calculated for once-daily forecasts from July 2005, and an adjoint is used to measure observation impacts of different data types. The forecast skill of the OSSE is found to be slightly higher than for real data, with smaller ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…The GMAO global OSSE has been extensively calibrated as documented by Prive´et al (2013c). The NR employed is a 13-month free forecast of the ECMWF operational model version c31r1, run at T511 horizontal resolution with 91 vertical levels and 3-hourly output.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GMAO global OSSE has been extensively calibrated as documented by Prive´et al (2013c). The NR employed is a 13-month free forecast of the ECMWF operational model version c31r1, run at T511 horizontal resolution with 91 vertical levels and 3-hourly output.…”
Section: Methodsmentioning
confidence: 99%
“…A cube-sphere grid with 180 gridpoints along each edge of the cube (approximately equivalent to 0.58 horizontal resolution at the equator) was employed with 72 hybrid vertical coordinate (h) levels. The forecast skill in the OSSE has been validated against the real world in the same manner as described by Prive´et al (2013c), with the forecasts in the OSSE found to have somewhat greater skill than for real data. The increased forecast skill is not expected to significantly impact the results of this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general GMAO OSSE development and validation efforts are described in Errico et al (2013) and Privé et al (2013a). Some improvements and the use of the OSSE to estimate analysis error are presented in Errico and Privé (2014).…”
Section: The Gmao Ossementioning
confidence: 99%
“…At NASA's GMAO, a framework for carefully validating and conducting an observing system simulation experiment (OSSE) has been developed (Errico et al, 2013;Privé et al, 2013a). Within that framework, background error can be precisely calculated because the truth is known explicitly.…”
Section: Introductionmentioning
confidence: 99%